Commodification of Personal Letters: The Cultural Politics of Print Industry in Nineteenth Century England - Acharya, Khagendra (Bodhi: An Interdisciplinary Journal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI: 10.3126/bodhi.v2i1.2869 Bodhi Vol.2(1) 2008 p.176-187